Sosialisasi Fungsi Google Map bagi Pengembangan Usaha Kalangan Ibu Rumah Tangga Pebisnis Online di Kota Makassar - Misbawati; Ahmadin (Insan Kreasi Media, 2022)
This community service article examines the importance of providing basic knowledge about the function and position of Google Maps in online business among housewives in Makassar City. As we all know that today's business activities have shifted to the virtual world and can be done anytime and anywhere. Online business opportunities or business activities in the virtual world can also be carried out by everyone provided they have the ability to manage and operate social media features. One important element that is part of an online business is a Google Map which is a marker point for the address of a company or business office. Thus, to increase consumer confidence, ideally a business should show its full address. For this purpose, it is necessary to understand how to make a google map and what the review function is for online business development. Increased knowledge about the benefits of Google Maps and the usefulness of reviews among housewives is carried out through outreach activities coupled with social gathering activities. The expected output of this activity is that online business people, namely housewives, have knowledge of the importance of Google Map in various activities or types of business.